Cellular Anti-Inflammatory and Antioxidant Activities of Bamboo Sasa albomarginata Leaf Extract and Its Constituent Coumaric Acid Methyl Ester - Shiori Kojima; Masatoshi Hakamata; Toshimichi Asanuma; Rie Suzuki; Jun-ichi Tsuruda; Takeshi Nonoyama; Yinzhi Lin; Hitomi Fukatsu; Naoki Koide; Kazuo Umezawa (The Scientific World Journal)
Background. Hot water extract of Sasa albomarginata (Kumazasa) leaves is commercially available and used as a dietary supplement or skincare cream. The extract possesses anti-inflammatory activity on the mouse atopic dermatitis model. To elucidate the mechanism of in vivo activity, we have studied the cellular anti-inflammatory and antioxidant activities of the extract and its constituents. Methods. Secretion of mouse and human IL-6 was measured by ELISA. ROS production was measured by a fluorescent reagent. Ultrahigh performance liquid chromatography (UHPLC)/MS was used for the ingredient analysis. Results. The Sasa albomarginata extract inhibited inflammatory mediators such as LPS-induced NO, IL-6, and ROS production in mouse monocyte leukemia RAW264.7 cells. It also inhibited iNOS, IL-6, and IL-1β expressions. Moreover, it inhibited LPS-induced IL-6 expression and production in human monocyte leukemia THP-1 cells differentiated into macrophages. The HPLC analysis of the extract revealed the existence of coumaric acid, ferulic acid, and coumaric acid methyl ester. Coumaric acid methyl ester but not coumaric acid or ferulic acid inhibited LPS-induced NO, IL-6, and ROS production in RAW264.7 cells and IL-6 production in differentiated THP-1 cells. Conclusion. The hot water extract of Sasa albomarginata leaves and one of its constituents possess cellular anti-inflammatory and antioxidant activities.